TLR4-Dependent DUOX2 Activation Triggered Oxidative Stress and Promoted HMGB1 Release in Dry Eye - Wang, Bowen; Zeng, Hao; Zuo, Xin; Yang, Xue; Wang, Xiaoran; He, Dalian; Yuan, Jin (Frontiers in Medicine, 2022)
Dry eye disease(DED) is one of the most common ocular surface diseases worldwide. DED has been characterized by excessive accumulation of reactive oxygen species (ROS), following significant corneal epithelial cell death and ocular surface inflammation. However, the key regulatory factor remains unclear. In this study, we tended to explore whether DUOX2 contributed to DED development and the underlying mechanism. Human corneal epithelial(HCE) cells was treated with hyperosmolarity, C57BL/6 mice were injected of subcutaneous scopolamine to imitate DED. Expression of mRNA was investigated by RNA sequencing (RNA-seq) and qPCR. Protein changes and distribution of DUOX2, HMGB1, TLR4, 4-HNE were evaluated by western blot assays and immunofluorescence. Cell death was assessed by CCK8, LDH release, and PI staining. Cellular reactive oxygen species (ROS) levels and mitochondrial membrane potential (MMP) were analyzed by flow cytometry. RNA-seq and western blot assay indicated a significant increase of DUOX2 dependent of TLR4 activation in DED both in vitro and in vivo. Immunofluorescence revealed significant translocation of HMGB1 within corneal epithelial cells under hyperosmolar stress. Interestingly, after ablated DUOX2 expression by siRNA, we found a remarkable decrease of ROS level and recovered MMP in HCE cells. Moreover, knockdown of DUOX2 greatly inhibited HMGB1 release, protected cell viability and abolished inflammatory activation. Taken together, our data here suggest upregulation of DUOX2 plays a crucial role in ROS production, thereafter induce HMGB1 release and cell death, which triggers ocular surface inflammation in DED.